Scientific Argumentation Profile of Senior High School Students - Indah Juwita Sari; Adzan Sa'ban; Siti Nur Allisa; Fifi Rahayu; Suppamai Promkaew (Jurnal Pendidikan Indonesia Gemilang, 2023)
This study aimed to describe students' scientific argumentation at the senior high school level. This study used a descriptive method and a test to assess the scientific argumentation of 49 students, consisting of eight questions from two themes. We used four components of scientific argumentation: students' ability to make claims and warrants, students' ability to construct counterarguments, students' ability to generate supportive arguments, and student's ability to generate evidence from Lin and Mintzes (2010). We quantified the qualitative data from students' answers and analyzed the data using descriptive statistics. The results showed that the scientific argumentation of senior high school students was 33% in the good category, 31% in the satisfactory category, 22% in the need improvement category, and 14% in the unsatisfactory category. For each component, 95% of students can make claims and warrants, 54% of students have the ability to construct counterarguments, 48% of students can generate supportive arguments, and 98% have the ability to generate evidence. So, the teacher needs to improve students' scientific literacy so students can give the argument with good references.